Phosphorimetric characterization of solution-processed polymeric oxygen barriers for the encapsulation of organic electronics - Aluicio-Sarduy, Eduardo; Baidak, Aliaksandr; Vougioukalakis, Georgios C.; Keivanidis, Panagiotis E. (My University, 2014)
We describe the use of a modified Stern-Volmer photokinetic model for the determination of the oxygen-permeation coefficient (PO2) of materials that can be used as barriers against oxygen permeation in organic electronic applications. The model is applied on photophysical data collected based on the use of the optical technique of phosphorimetry for the oxygen-sensing organometallic complex (2,3,7,8,12,13,17,18-octaethylporphyrinato)platinum(II) (PtOEP). PtOEP is used as a phosphorescent probe encapsulated by a set of model solution-processed transparent oxygen-barrier layers made by the polymers of poly(norbornene), poly(methyl methacrylate), poly(styrene), and Zeonex. For each barrier system the oxygen-induced quenching of the PtOEP phosphorescence is monitored with the study of the time-integrated and time-resolved PtOEP phosphorescence intensity, as a function of the partial pressure of oxygen. The advantage of utilizing the presented photokinetic model is based on the consideration of the fractional accessibility of the excited triplet states to the permeant oxygen. The extracted values of PO2 are in excellent agreement with the previous literature, confirming the validity of the modified Stern-Volmer model employed in the analysis of the photophysical data. The results suggest that phosphorimetric characterization is a simple and inexpensive methodology for the fast screening of next-generation barrier materials for organic electronic devices. The high sensitivity of the phosphorimetric technique is shown in the successful characterization of a commonly used glass/epoxy barrier system for which PO2 = 39 × 10-16 cm3 (STP) ·cm·cm -2·s-1·Pa-1 is found. The findings of the phosphorimetric characterization are in qualitative agreement with a preliminary shelf lifetime stability test of organic solar cell devices that were encapsulated with some of the barrier materials of the study. © 2014 American Chemical Society.
Keywords: Barrier materials; Degradation; Oxygen permeation; Phosphorimetry; Organic solar cells; Organic electronics; Stability